Design, synthesis and antibacterial activity of chalcones against MSSA and MRSA planktonic cells and biofilms - Garcia, Mayara A.R. [UNESP]; Theodoro, Reinaldo S. [UNESP]; Sardi, Janaina C.O.; Santos, Mariana B. [UNESP]; Ayusso, Gabriela M. [UNESP]; Pavan, Fernando R. [UNESP]; Costa, Alan R.; Santa Cruz, Lucas M.; Rosalen, Pedro L.; Regasini, Luis O. [UNESP] (Elsevier, 2021)
Staphylococcus aureus is the one of the most successful modern pathogens. The same bacterium that lives as a skin and mucosal commensal can be transmitted in health-care and community-settings and causes severe infections. Thus, there is a great challenge for a discovery of novel anti-Staphylococcus aureus compounds, which should act against resistant strains. Herein, we designed and synthesized a series of 17 chalcones, substituted by amino group on ring A, which were evaluated against methicillin-susceptible S. aureus (MSSA) and methicillin-resistant S. aureus MRSA planktonic cells. The antibacterial potency was improved by substituents on ring B, which were designed according to Topliss’ manual method. 4-bromo-3′-aminochalcone (5f) was the most active, demonstrating minimum inhibitory concentration (MIC) values of 1.9 μg mL−1 and 7.8 µg mL−1 against MSSA and MRSA, respectively. The association of 5f with vancomycin demonstrated synergistic effect against MSSA and MRSA, with Fractional Inhibitory Concentration Index (FICI) values of 0.4 and 0.3, respectively. Subinhibitory concentration of 5f inhibited the MSSA and MRSA adhesion to human keratinocytes. Chalcone 5f was able to reduce MSSA and MRSA biofilm formation, as well as acts on preformed biofilm in concentration-dependent mode. Scanning electron microscopy analyses confirmed severe perturbations caused by 5f on MSSA and MRSA biofilm architecture. The acute toxicity assay, using Galleria mellonella larvae, indicated a low toxic effect of 5f after 72 h, displaying lethality of 20% and 30% at 7.8 μg mL−1 and 78.0 μg mL−1, respectively. In addition, the antibacterial activity spectrum of 5f indicated action against planktonic cells of Enterococcus faecalis (MIC = 7.8 μg mL−1), Acinetobacter baumannii (MIC = 15.6 μg mL−1) and Mycobacterium tuberculosis (MIC = 5.7 μg mL−1). Altogether, these results open new avenues for 5f as an anti-Staphylococcus aureus agent, with potential applications as antibacterial drug, adjunct of antibiotics and medical devices coating.
Keywords: Antibacterial; Biofilm; Chalcone; MRSA; Staphylococcus aureus; Topliss